Jenis-Jenis Jamur Makroskopis Yang Ditemukan Di Jorong Sungai Pangalek Nagari Sariak Alahan Tigo Kecamatan Hiliran Gumanti Kabupaten Solok - Ranti Saptira; Aulia Afza; Nursyahra Nursyahra (Symbiotic: Journal of Biological Education and Science, 2021)
Fungi are eukaryotic organisms that do not have green leaf substance (chlorophyll), have different shapes and sizes, are unicellular and multicellular in addition to fungi also do not like light. The Jorong River Pangalek Forest Area is one of the places that has high humidity and low temperature. This is because the forest area has dense trees and shrubs. This research was conducted in January 2021, using a descriptive survey for field sampling using the tracking method on a radius of 10 meters to the left and to the right along the predetermined research path. Sample identification was carried out at the Botany (Biology) Laboratory of STKIP PGRI West Sumatra. The results of the research that have been obtained in the Jorong Sungai Pangalek Forest area found 28 types of macroscopic fungi belonging to 2 divisions, 5 classes, 9 orders, 13 families and 21 genera. Environmental factors that affect the air temperature ranges from 210C-250C, humidity ranges from 28% - 35%, and soil pH around 6.4 - 6.6. Based on these results, it shows that the Jorong River Pangalek Forest area has a variety of macroscopic types of fungi.